Academic well-being and smoking among 14- to 17-year-old schoolchildren in six European cities - Kinnunen, Jaana M. (2018)
It is well established that poor academic performance is related to smoking, but the association between academic well-being and smoking is less known. We measured academic well-being by school burnout and schoolwork engagement and studied their associations with smoking among 14- to 17-year-old schoolchildren in Belgium, Germany, Finland, Italy, the Netherlands, and Portugal. A classroom survey (2013 SILNE survey, N = 11,015) was conducted using the Short School Burnout Inventory and the Schoolwork Engagement Inventory. Logistic regression, generalized linear mixed models, and ANOVA were used. Low schoolwork engagement and high school burnout increased the odds for daily smoking in all countries. Academic performance was correlated with school burnout and schoolwork engagement, and adjusting for it slightly decreased the odds for smoking. Adjusting for socioeconomic factors and school level had little effect. Although high school burnout and low schoolwork engagement correlate with low academic performance, they are mutually independent risk factors for smoking.